2001
DOI: 10.1248/bpb.24.921
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Neurotrophic Effects of Quinic Acids from Aster scaber in PC12 Cells.

Abstract: Aster scaber T. (Asteraceae) has been used to treat bruises, snakebite, headache, and dizziness in traditional Chinese medicine. In the present study, the neuroprotective effect of four quinic acid derivatives from A. scaber on amyloid Abeta-induced PC12 cell toxicity was investigated. When cells were treated with quinic acid derivatives prior to Abeta, cell toxicity was significantly diminished. Among quinic acid derivatives, (-)4,5-dicaffeoyl quinic acid (1) gave the highest protection against Abeta-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…Caffeoylquinic acid derivatives, like 3-O-caffeoylquinic acid (3-CQA), 5-O-caffeoylquinic acid (5-CQA) and 3,5-di-O-caffeoylquinic acid (3,, are natural pohenolic compounds that have been isolated from a variety of traditional medicine plants and present a broad spectrum of pharmacological properties, including antioxidant, hepatoprotectant, antibacterial, antihistaminic and other biological effects (Basnet, Matsushige, Hase, Kadota, & Namba, 1996;Kwon, Jung, & Shin, 2000). Recently, it has been demonstrated that caffeoylquinic acid derivatives possess also neuroprotective effects (Hur, Soh, & Kim, 2001;Soh, Kim, Sohn, Lee, & Kim, 2003). More, it is reported that 3,5-diCQA exhibited neuroprotective properties against neuronal cell death that can be applied in the development of brain protection, as well as in the treatment of neurodegenerative diseases, such as Alzheimer's disease, Parkinson's disease and ischemia (Kim, Park, Jeon, Kwon, & Chun, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeoylquinic acid derivatives, like 3-O-caffeoylquinic acid (3-CQA), 5-O-caffeoylquinic acid (5-CQA) and 3,5-di-O-caffeoylquinic acid (3,, are natural pohenolic compounds that have been isolated from a variety of traditional medicine plants and present a broad spectrum of pharmacological properties, including antioxidant, hepatoprotectant, antibacterial, antihistaminic and other biological effects (Basnet, Matsushige, Hase, Kadota, & Namba, 1996;Kwon, Jung, & Shin, 2000). Recently, it has been demonstrated that caffeoylquinic acid derivatives possess also neuroprotective effects (Hur, Soh, & Kim, 2001;Soh, Kim, Sohn, Lee, & Kim, 2003). More, it is reported that 3,5-diCQA exhibited neuroprotective properties against neuronal cell death that can be applied in the development of brain protection, as well as in the treatment of neurodegenerative diseases, such as Alzheimer's disease, Parkinson's disease and ischemia (Kim, Park, Jeon, Kwon, & Chun, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing attention has been directed to CGA (the ester of caffeic acid with quinic acid), given its high abundance in coffee, its antioxidant activity (Gomez-Ruiz et al 2007;Zang et al 2003), and the suggestion that CGA and/or its metabolites are bioavailable in brain tissue (de Paulis et al 2002). CGA and its derivatives have displayed antioxidant and neuroprotective properties in models of neurodegenerative and pathological disease (Chu et al 2009;Han et al 2010;Hur et al 2001;Kim et al 2005;Silva et al 2004). In addition, there are reports of behavioral effects of CGA including the demonstration that CGA and/or its derivatives reduce anxiety-related behavior (Bouayed et al 2007), improve spatial learning and memory (Han et al 2010), and reduce behavioral deficits (Lapchak 2007) in a variety of in vivo animal models of disease or behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that caffeoylquinic acid derivatives possess neuroprotective effects in Aβ-induced PC12 toxicity (Hur et al, 2001) and tetrahydropapaveroline (THP)-induced C6 glioma cell death (Soh et al, 2003). However, the mechanism by which these caffeoylquinic acid derivatives exert neuroprotection is unclear.…”
Section: Introductionmentioning
confidence: 99%